1970
DOI: 10.4314/ajns.v29i2.70403
|View full text |Cite
|
Sign up to set email alerts
|

Facteurs predictifs de mortalite par accident vasculaire cerebral (AVC) a la Clinique Neurologique du chu de Fann, Dakar - Senegal

Abstract: Description Les AVC constituent un problème de santé publique avec une mortalité élevée. Objectif Identifier les facteurs prédictifs de mortalité par accidents vasculaires cérébraux à la Clinique Neurologique du CHU de Fann, Dakar. Méthodes Il s’agit d’une étude rétrospective du 1er Janvier 2001 au 01 Novembre 2003 portant sur des patients avec AVC et ayant eu un examen tomodensitométrique cérébral. Les données sociodémographiques, les antécédents médicaux et chirurgicaux, les signes de gravité associés au tab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Regarding sex, we found that men were the most represented in our sample without a statistically significant difference. This finding is consistent with descriptions by some authors in Congo (62.70 years) in Central Africa [14], Dakar (61.3 years) and Mauritania (58 years) in West Africa [15] as in the West [16], apart from Touré et al who have regained a female predominance [10]. For this variable, it is merely a finding which has no scientific explanation.…”
Section: Age and Sexsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding sex, we found that men were the most represented in our sample without a statistically significant difference. This finding is consistent with descriptions by some authors in Congo (62.70 years) in Central Africa [14], Dakar (61.3 years) and Mauritania (58 years) in West Africa [15] as in the West [16], apart from Touré et al who have regained a female predominance [10]. For this variable, it is merely a finding which has no scientific explanation.…”
Section: Age and Sexsupporting
confidence: 92%
“…This study shows that the average age of stroke patients was 63.15 years with extremes of 38 and 91 years. These data overlap with those described, both in Africa [10] [14] [15] and in the West [16] and Middle East [17]. This great age confirms the influence of this variable as a risk factor for stroke and corroborates the data of literature [18].…”
Section: Age and Sexsupporting
confidence: 90%
See 1 more Smart Citation
“…Ischemic stroke was predominantly noted in our study. The same is true of work done in Nouakchott [19], Dakar [20], Singapore [21]. But other authors have noted a predominance of hemorrhagic strokes [13] [22]; other old studies reporting a high proportion of hemorrhagic strokes.…”
Section: Discussionmentioning
confidence: 62%
“…But for Longo-Menza [26], ischemic strokes are associated with higher mortality, whereas, according to Ong et al [19], the hematomas are associated with it.…”
Section: Discussionmentioning
confidence: 99%